ANALISIS PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN MOBIL CITY CAR DAIHATSU AYLA KATEGORI LOW COST GREEN CAR (LCGC) (Studi Kasus PT Serba Mulia Auto di Kabupaten Mimika) - Christy Mononutu; Siske Tontong (CV. Adiba Aisha Amira, 2023)
This research aims to determine the influence of brand equity on purchasing decisions for the Daihatsu Ayla city car in the low cost green car (LCGC) category in Mimika Regency. The method used is the associative method, namely the method used to determine the relationship between two or more variables. The population in this study were consumers or users of the Daihatsu Ayla city car in the low cost green car (LCGC) category with a sample of 60 respondents. Sampling used a simple random sampling technique. Data collection techniques use interview techniques, questionnaires and literature studies. To test the data in this research using validity tests and reliability tests. The data analysis technique used in this research is multiple linear regression analysis technique. The results of this study show that brand awareness (X1), brand association (X2), and perceived quality (X3) have a significant effect on the decision to purchase the Daihatsu Ayla city car in the low cost green car (LCGC) category, while brand loyalty (X4) has no effect.